(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Both Joseph Conrad (1857–1924) and Chinua Achebe (1930–2013) focus on the roles of dominant men towards other less important men or women in their novels to further illustrate that people change their attitudes, responsibilities, and relationships in society according to their gender due to the effect of colonization. Hence, the present paper studies the similarities and differences of the gender roles in male characters in Conrad’s The Heart of Darkness (1899) and Achebe’s Things Fall Apart (1958) and traces their importance and influence on clarifying the themes of the novels. To analyze gender roles in detail in terms of Connell’s hegemonic masculinity, the paper argues that men vary across time, culture, and individual, and their roles legitimize their status in society and marginalize others in society.